Investigation on Nonuniform Extension of Hydraulic Fracture in Shale Gas Formation - Zhiheng Zhao; Youcheng Zheng; Yili Kang; Bo Zeng; Yi Song (Geofluids)
Hydraulic fracturing with multiple clusters has been a significant way to improve fracture complexity and achieve high utilization of shale formation. This technology has been widely applied in the main shale area of North America. In Changning shale block of China, it, as a promising treatment technology, is being used in horizontal well now. Due to the anisotropy of mechanical property and the stress shadowing effect between multiclusters, fractures would extend nonuniformly and even some clusters are invalid, leading to a poor treatment performance. In this work, based on the geology and engineering characteristics of Changning shale block, different cluster number, cluster spacing, perforation distribution, and flow rate were discussed by the numerical simulation method to clarify multifracture propagation. It is implied that with the reduction of cluster number and the growth of cluster spacing and flow rate, the length and average width of interior fractures are inclined to increase due to the mitigation of stress shadowing effect, contributing to the lower standard deviation (SD) of fracture length, but too small cluster number or too large cluster spacing is not recommended. Besides, the perforation distribution with more perforations in interior fractures can get larger length and average width of interior fractures compared with another two perforation distributions because of more fractional flow rates obtained, which results in more even fracture propagations. In Changning shale block, multicluster hydraulic fracturing with 4-6 clusters in a stage has been employed in 300-400 m well spacing, and diversion technology, limited-entry perforation (36-48 perforations per stage), high flow rate (16 m3/min), and small-sized ceramic proppant (100 mesh) are used to get better shale gas production. To promote the even propagation of fractures further, nonuniform perforation distribution should be introduced in the target shale area.